PENGARUH AKSES PAJAK, FASILITAS, SOSIALISASI PERPAJAKAN DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Handayani Barus, Stephanie Amelia; Anisma, Yuneita; ', Kamaliah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
Motor vehicle tax is one of the biggest contributor in original income for finance regional development areas of the province. Therefore the admission should continue to optimized in order to reach the target expected by the local government. This study aims to examine the influence of tax access, facilities, taxation socialization and quality of service on compliance compulsory motor vehicle tax. The population of this study is the tax payers of the registered motor vehicleon SAMSAT office in Pekanbaru. The technique of data collection on these studies is uses convenience sampling method and calculation of determining the sample uses Slovin Formula so that the number of samples used are 100 respondents. The type of data in this study are primary data that using questionnaires and analyzed by using SPSS 20. Then, the data analyzed for hypothesis testing using multiple linear regression analysis approach. The results of this research found that access taxes, facilities, and quality of service affect compliance compulsory motor vehicle tax at the level of significance5% (b1= 3,479, b2= 3,068, b4= 2,512). Otherwise, taxation socialization do not affect compliance compulsory on the level of significance of 5% (b3= 0,819).Keywords: Access taxes, facilities, quality of service, taxation of socialization, and taxpayer compliance